Handbook of psychopathy - Patrick, Christopher J. (The Guilford Press, 2007)
Provides a review of knowledge on the psychopathic personality. This work covers major theoretical models; conceptual and definitional questions; assessment approaches; and, etiological pathways, ranging from family and environmental factors to genes, neurotransmitters, and brain systems.